Antimicrobial Activities of Stigmasterol from Piper crocatum In Vitro and In Silico - Seftiana Lestari; Dikdik Kurnia; Tri Mayanti; Leny Heliawati (Journal of Chemistry)
The high incidence of oral health issues and antibiotic resistance has stimulated research into discovering novel antimicrobial drugs. Prior evidence suggests that red betel leaves (Piper crocatum Ruiz and Pav) possess potential antimicrobial properties, including the presence of stigmasterol, a bioactive compound. However, the proteins precisely inhibited by stigmasterol compounds have not been identified as target proteins in the mechanism of action of stigmasterol as an oral antimicrobial agent or proteins involved in the virulence system of pathogenic oral microorganisms. The objective of this research is to identify and predict the antimicrobial mechanism of action of the stigmasterol compound isolated from red betel against specific proteins using a molecular docking approach. The methods employed for this investigation are as follows: Stigmasterol extracted from P. crocatum Ruiz and Pav was utilized as a ligand. Positive controls for each protein were antibiotics or substrates. The study findings indicate that the stigmasterol compound exhibits antibacterial and antifungal properties against pathogenic oral microorganisms in vitro as well as in silico against the crucial antibacterial enzymes MurA and PBP in addition to the pivotal antifungal enzyme exo-β-1,3-glucanase and lanosterol-14-α-demethylase. Therefore, it can be inferred that the stigmasterol present in Red Betel leaves could potentially function as an antimicrobial agent by impeding the spread of pathogenic oral microorganisms.